Schizophrenia: Genetics, neurological mechanisms, and therapeutic approaches - Debbie Xiu En Lim; Shi Yun Yeo; Zhen You Ashley Chia; Aaron Zefrin Fernandis; Jimmy Lee; John Jia En Chua (Neural Regeneration Research, 2026)
Schizophrenia is a complex psychiatric disorder marked by positive and negative symptoms, leading to mood disturbances, cognitive impairments, and social withdrawal. While anti-psychotic medications remain the cornerstone of treatment, they often fail to fully address certain symptoms. Additionally, treatment-resistant schizophrenia, affecting 30%–40% of patients, remains a substantial clinical challenge. Positive, negative symptoms and cognitive impairments have been linked to disruptions in the glutamatergic, serotonin, GABAergic, and muscarinic pathways in the brain. Recent advances using genome-wide association study and other approaches have uncovered a significant number of new schizophrenia risk genes that uncovered new, and reinforced prior, concepts on the genetic and neurological underpinnings of schizophrenia, including abnormalities in synaptic function, immune processes, and lipid metabolism. Concurrently, new therapeutics targeting different modalities, which are expected to address some of the limitations of anti-psychotic drugs currently being offered to patients, are currently being evaluated. Collectively, these efforts provide new momentum for the next phase of schizophrenia research and treatment.